SEASONAL VARIATIONS OF VIVAX AND FALCIPARUM MALARIA: AN OBSERVATION AT A TERTIARY CARE HOSPITAL - Jamil, Shahid; Khan, Muhammad Nawaz (Journal of Ayub Medical College Abbottabad, 2012)
Background: Malaria is a major public health problem in the malaria endemic zones of the world. Various factors influence the prevalence of malaria. This study was conducted to determine the variation in frequency of Plasmodium vivax and Plasmodium falciparum malaria in different seasons of the year in Khyber Teaching Hospital, Peshawar. Methods: A total of 411 patients were included in the study. All these febrile patients were reported to have trophozoites of either Plasmodium vivax or Plasmodium falciparum malaria on Giemsa stained thick and thin smears. The frequency of vivax and falciparum malaria was worked out and statistically analysed for different season of the year. The study was carried out from 2nd Jan 2004 till 31st December 2008. Results: Out of total 411 diagnosed malaria cases, total 134 (32.60%) presented in the autumn season (vivax=33.58%, and falciparum=66.42%), 37 (9%) in winter season (vivax=32.4%, and falciparum=67.6%), 76 (18.49%) in spring season (vivax=93.4% and falciparum 6.6%) and 164 (39.90%) in summer season (vivax=89.6, and falciparum=10.4%). The malaria showed a highly significant pattern in different seasons of the year (p=0.00) in a way that Plasmodium falciparum malaria reached its highest frequency in autumn and winter seasons while Plasmodium vivax malaria reached its peak frequency in spring and summer seasons. Conclusion: There was highly significant seasonal variation of vivax and falciparum malaria. There is arrival of Plasmodium falciparum in autumn which peaks in winter followed by arrival of Plasmodium vivax in spring till the end of summer. Keywords: Malaria, Falciparum, Vivax, Peshawar